MODIFIKASI GAYA BUSANA CLEOPATRA PADA BUSANA PESTA MODEL STRAPLESS - Nusaibah, Aisyah; Wiana, Winwin (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2024)
Ancient Egyptian culture is one of the oldest and most advanced cultures in the world, reflecting advances in areas such as the construction of monuments, knowledge of mathematics, art and architecture, and dress code. Ancient Egyptian clothing reflects the rich culture and long history of Egyptian civilization. Cleopatra, the legendary Queen of Ancient Egypt, was the inspiration for this iconic style of clothing that combines ancient Egyptian elements with a modern touch, creating a graceful and luxurious look using a strapless model. The aim of this research is to hope that by using a strapless model for this clothing, a product can be developed in the form of evening party clothing based on the idea of Cleopatra's clothing from ancient Egypt without leaving behind the characteristics of Cleopatra's clothing. The method used in making party clothing is the work creation method. This method has 4 stages, namely: pre-design, design, realization and presentation. Cleopatra's party attire was completed with a validity test for the general public to demonstrate the appropriateness of the party attire to the general public. This method refers to the relevance of unique and distinctive characteristics in clothing. So the results of this research show that the product produced is appropriate and the clothing produced is good. Keywords: Egypt, party fashion, cleopatra, strepless.